Improving Students’ Speaking Skills Through Continuous Story Technique With Pictures - Razaq, Yusuf; Asyurah, Suci; Amiruddin, Amiruddin; Satriani, Satriani; Nurhidayanti, Nurhidayanti (ETDC: Indonesian Journal of Research and Educational Review, 2022)
Using the continuous tale technique in the classroom, this research describes the students' speaking abilities. Its goal is to obtain answers to the following study question: "Does the use of continuous story approach increases the students' speaking skills in the sixth semester of English education at IAI As'adiyah Sengkang?" The author used the pre-experimental approach in this study, which included a pretest, posttest, and therapy. A purposive sampling strategy was used to choose the sample of 13 pupils. The speaking test, which measures accuracy, fluency, and comprehensibility, was used in this study. SPSS was used to collect and analyze the data from the pretest and posttest. The mean score of the pre-tests was 41.50, while the post-test was 72.00, according to the data analysis. It means that the mean scores between them have improved. The standard deviation was 11.649 in the pretest and 8.195 in the posttest. Furthermore, the posttest's t-test value was 0.00, which was less than 0.05. As a result, the continuous tale strategy was found to improve speaking.